Tumor Site‐Specific In Vivo Theranostics Enabled by Microenvironment‐Dependent Chemical Transformation and Self‐Amplifying Effect - Yunfei Zuo; Pei Li; Wen‐Jin Wang; Changhuo Xu; Shuting Xu; Herman H. Y. Sung; Jianwei Sun; Guorui Jin; Weiping Wang; Ryan T. K. Kwok; Jacky W. Y. Lam; Ben Zhong Tang (Advanced Science)
Abstract Precise tumor diagnosis and treatment remain complex challenges. While numerous fluorescent probes have been developed for tumor‐specific imaging and therapy, few exhibit effective function in vivo. Herein, a probe called TQ‐H2 is designed that can realize robust theranostic effects both in vitro and in vivo. In vitro, TQ‐H2 specifically targets the lysosome and reacts with hydroxyl radical (·OH) to generate TQ‐HA, which lights up the cells. TQ‐HA generates reactive oxygen species (ROS) under light irradiation, enabling the simultaneous induction and monitoring of apoptosis and ferroptosis in tumor cells. Remarkably, TQ‐HA also acts as a self‐amplifier, autocatalytically activating TQ‐H2 by generating ·OH under light exposure. This self‐amplification aligns with the tumor microenvironment, where TQ‐H2 undergoes chemical transformation, distinguishing tumors from healthy tissue via near‐infrared (NIR) fluorescence imaging. Furthermore, ROS generated by TQ‐HA effectively kills tumor cells and inhibits tumor growth without harming normal cells. This study offers a promising strategy for targeted tumor theranostics using self‐amplifying microenvironment‐responsive fluorescent probes.